The evolution of referees in the English Premier League - Webb, T. (Soccer & Society, 2022)
Despite their importance, referees are an often overlooked part of professional football. Referees are an integral part of the global game and are required for fixtures to take place and competitions to occur. The English Premier League (EPL) provides a unique backdrop to consider the development of referees within the league, from the formation up until the present day. Referees have dealt with numerous changes, developments and technological advancements and continue to operate and perform at the highest level, required to officiate in the EPL. However, the continued growth of the EPL has also led to associated challenges for referees and a constant presence in the media with their decisions scrutinized in detail. This article considers the evolution of refereeing in the EPL, examines some of the most significant changes that have impacted upon refereeing and identifies some of the current challenges and opportunities that might exist for refereeing in the EPL.